Economic Compatibility of Islamic Economy and Pancasila: Implications for the Postgraduate Curriculum - Amalia, Euis; Musa, Eltom Ishaq Osman (Indonesian Journal of Islamic Economic Law, 2024)
This article aims to develop the Sharia Economics Curriculum in Indonesia which has a unique relationship between religion and state and the compatibility of both in the postgraduate curriculum in Indonesia. The integration of Islamic Economic values into the Pancasila economic framework supports the Islamic economic industry in Indonesia. The analytical method in this study will utilize literature studies by collecting and evaluating relevant theoretical sources to understand the compatibility between Pancasila economics and Islamic economics. The data will be analyzed through classification, synthesis, and pattern tracing in the literature to fill the research gap. The research concluded that there are several critical points in the alignment of the curriculum of the Master of Sharia Economic Law in Indonesia, including discrepancies in the integration of the economic values of Pancasila and Islamic Economics, a focus on legal aspects rather than ethics, a lack of concretomatic details on the redistribution of wealth and property rights, and a lack of emphasis on social welfare. The recommendations involve developing detailed strategies to integrate these values into the curriculum, collaboration with Islamic economic experts, practitioners, and experts, and ongoing monitoring and evaluation to ensure comprehensive alignment. It is necessary to create graduates with a holistic understanding of the compatibility of Islamic Economics and Pancasila in Islamic economic law.